Factors Influencing Customer Continuance Intention in Using E-Money Application: Case of Jakarta - Pantri Heriyati, Nur AsiahAyu Tri Jaya, Janice Michelle Ticoalu, Apriani Kurnia Suci (International Journal of Advanced Science and Technology, 2020)
This research aims to explore the influence of network externalities, perceived complementarity, perceived ease of use, perceived usefulness, and perceived value have an influence on the user's continuance intention of the e-money OVO brand.